2016
DOI: 10.1016/j.jfda.2016.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of polyphenol-enriched extract from Ziyang tea against human breast cancer MCF-7 cells through reactive oxygen species-dependent mitochondria molecular mechanism

Abstract: A polyphenol-enriched extract from selenium-enriched Ziyang green tea (ZTP) was selected to evaluate its antitumor effects against human breast cancer MCF-7 cells. In ZTP, (-)-epigallocatechin gallate (28.2%) was identified as the major catechin, followed by (-)-epigallocatechin (5.7%) and (-)-epicatechin gallate (12.6%). ZTP was shown to inhibit MCF-7 cell proliferation (half maximal inhibitory concentration, IC = 172.2 μg/mL) by blocking cell-cycle progression at the G0/G1 phase and inducing apoptotic death.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 56 publications
0
29
0
Order By: Relevance
“…In 2016, Li et al demonstrated that green tea preparation influenced internal oxidative stress of MCF-7 cells with an approximately 11-fold increase in ROS accumulation at 50 mg/mL dosage of preparation. Payen et al showed that in SiHa-F3 cells EGCG at concentrations of 100 nM, 1 μM, 10 μM and 100 μM revealed a growing antioxidant effect which was correlated with the EGCG concentration [26].…”
Section: Resultsmentioning
confidence: 99%
“…In 2016, Li et al demonstrated that green tea preparation influenced internal oxidative stress of MCF-7 cells with an approximately 11-fold increase in ROS accumulation at 50 mg/mL dosage of preparation. Payen et al showed that in SiHa-F3 cells EGCG at concentrations of 100 nM, 1 μM, 10 μM and 100 μM revealed a growing antioxidant effect which was correlated with the EGCG concentration [26].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies suggest that EGCG, EGC, ECG, EC, and C are the major catechins in tea, with their antioxidant activities demonstrated in the following order: EGCG > ECG > EGC > EC > C (Li et al, ; Spadiene et al, ). It is widely recognized that polyphenols of different molecular structures present different antioxidant activities.…”
Section: Resultsmentioning
confidence: 98%
“…Although the dark tea infusion did contain EGCG, its concentration was very low, resulting in quantitative analysis failure in some cases (Tables and ). It is well known that catechin compounds (EGCG, ECG, EGC, EC) are the most abundant flavonoids in tea (Li, He, Tian, Shi, & Yang, ); however, they are degraded by microbial enzymes and autoxidized during the fermentation process of black and dark teas (Jiang et al, ). In particular, EGCG can be metabolized by microorganisms to gallic acid and other compounds (Jiang et al, ; Takagaki, Kato, & Nanjo, ).…”
Section: Resultsmentioning
confidence: 99%
“…A diverse array of compounds with numerous biological properties account for these potential benefits. Phytochemicals, including flavonoids found in tea, have proven effective against chronic diseases, including colon cancer [33].…”
Section: Discussionmentioning
confidence: 99%